#TITLE_ALTERNATIVE# - SULISTYO (NIM 25106024), TEGUH
The presences of shopping area will indirectly provide a sufficient potential revenue for government. One of potential income from this typical property is Land and Building Tax because strategic location and high accessibility. Taxation base is the selling value of tax object (NJOP). As long as to determine NJOP for shopping center area can be considered with land value around although for other usage. It creates accurate and proper problems for NJOP. The objective of this research is to analyze influence of land value determinant for shopping center. Variables in study include distance to nearest central business district, nearest with other shopping area, density of people, building area coefficient, width of road, environment safety, environment comfortable, and allocation uniformity with area layout planning. Used data analysis is multiple regression analysis with ordinary least square. Used regression model is linear model. Used test model is apriority criteria test, statistic test, classic test, and model evaluation. The result of study yields the best linear modelling with mathematic equation: NT= 1.5437.210 - 579JCBD + 12.409 KPL + 65.620 LJ + 355.819 AL + for Karees area wholly with model ability in describing land value change as much as 68,32% (Adjusted R2). Significance influence variable is distance to local business center nearest, nearness with other shopping center, width of road, and environment safety. The second model NT = 173.399 + 19.952 KPL + 138.636 LJ + for Regol Sub district with model ability in describing land value change as much as 87,93%. Significance influence variable is nearness with other shopping center and width of road. The third model for Lengkong Sub district is NT = 753.512 + 12.070 KPL + 502.176 KLB + 157.312 LJ + . Significance influence variable is nearness with other shopping center, building area coefficient, and width of road, with model ability in describing land value change as much as 68,44%.